Antimicrobial peptides from Burkholderia arboris RAI16 inhibit diabetic wound pathogens. (2020) - Mohd Nor Hamin, Nurhanis Syafiqah; Wan Ahmad, Wan Nor Amaliena; Rohaini, Muhamad Raizal Azrai; Leong, Chean Ring; Md Abu, Taher; Tong, Woei Yenn
Abstract: The occurrence of diabetic mellitus has affected millions of populations worldwide with global estimation of 6.4%, hence affecting 285 million adults in 2010. Foot ulceration and wound infection are major forms of complications prevalence to diabetic mellitus which is due to microbial infections. Approximately 20% of moderate or severe diabetic foot ulcer lead to some level of amputation. In this study, we aimed to isolate potential AMP produced by Burkholderia arboris RAI16, a bacterium previously isolated from the mucus of L. terrestris . The crude peptides of B. arboris exhibited significant antimicrobial activity against all 9 test microorganisms. However, the size of inhibition zones varied among all the microorganisms, indicating different susceptibility of the test microorganisms to the crude peptides. Among the microbial species, the largest inhibition zone was observed on P. mirabilis . Enzymatic digestion of the crude peptides revealed that activity was significantly affected by the treatment with trypsin, protease and Proteinase K, confirming the proteinaceous nature of the compound. A total of 120 fractions were collected from ion exchange chromatography. However, only three fractions (Fraction 41, 113 and 118) contain anionic peptides that exhibited significant active inhibitory activity on P. mirabilis . In conclusion, AMPs produced by B. arboris RAI16 showed significant inhibitory effect on diabetic wound microorganisms. Further investigations should be conducted to identify the isolated AMPs to provide an alternative solution for diabetic wound infections.